2009
DOI: 10.1186/1477-7827-7-20
|View full text |Cite
|
Sign up to set email alerts
|

Early-cleavage is a reliable predictor for embryo implantation in the GnRH agonist protocols but not in the GnRH antagonist protocols

Abstract: Background: To test if early-cleavage was a strong predictor of pregnancy in patients receiving either a GnRH agonist long protocol or a GnRH antagonist protocol for in-vitro fertilization treatment (IVF) and intracytoplasmic sperm injection (ICSI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The first cleavage can be examined with the breakdown of the pronuclear membrane (the start of the M phase of the first cell cycle) and directly with the presence of cleavage, because the duration of the M phase is relatively constant (3-4 hours) [ 30 , 31 ]. It is known that early cleavage is a strong indicator of the quality and the viability of the embryos [ 30 , 32 , 33 ], although a recent study showed higher implantational potential for early-cleavage embryos only with the use of GnRH agonists [ 34 ]. We observed significantly higher number of blastomers in the antagonist group on day 2, while the higher presence of early cleavage in this group did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The first cleavage can be examined with the breakdown of the pronuclear membrane (the start of the M phase of the first cell cycle) and directly with the presence of cleavage, because the duration of the M phase is relatively constant (3-4 hours) [ 30 , 31 ]. It is known that early cleavage is a strong indicator of the quality and the viability of the embryos [ 30 , 32 , 33 ], although a recent study showed higher implantational potential for early-cleavage embryos only with the use of GnRH agonists [ 34 ]. We observed significantly higher number of blastomers in the antagonist group on day 2, while the higher presence of early cleavage in this group did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Patients ( n = 40) undergoing intracytoplasmic sperm injection (ICSI) treatments at the Center of Reproductive Medicine, Mackay Memorial Hospital, Taiwan received controlled ovarian hyperstimulation using the gonadotropin-releasing hormone antagonist protocol as described previously [ 27 ]. All patients were younger than 38 years.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies have shown that GNRH antagonist is responsible for an inhibitory effect on pre-implantation development of mouse embryos . In an attempt to explain such results, Yang et al (2009) have recently hypothesised that GNRH antagonists could interfere with cell growth by decreasing the synthesis of insulinlike growth factor (IGF) and epidermal growth factor receptors, which are involved in the MAP kinasemediated mitogenic cascade. However, the developmental potential of human pre-implantation embryos does not seem to be limited by putative detrimental effects of GNRH antagonist (Yang et al 2009).…”
Section: How Does Ovarian Stimulation Affect Early Oocyte and Embryo mentioning
confidence: 99%
“…In an attempt to explain such results, Yang et al (2009) have recently hypothesised that GNRH antagonists could interfere with cell growth by decreasing the synthesis of insulinlike growth factor (IGF) and epidermal growth factor receptors, which are involved in the MAP kinasemediated mitogenic cascade. However, the developmental potential of human pre-implantation embryos does not seem to be limited by putative detrimental effects of GNRH antagonist (Yang et al 2009). Additionally, high doses of GNRH antagonist were shown not to harm the implantation potential of embryos in frozenthawed cycles (Kol et al 1999), and a recent metaanalysis showed no significant differences in live birth rates following co-treatment with GNRH agonists versus GNRH antagonists (Kolibianakis et al 2006).…”
Section: How Does Ovarian Stimulation Affect Early Oocyte and Embryo mentioning
confidence: 99%